Neural Processing Letters - Verleysen, Michel; Hassoun, Mohamad H.; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
Neural Processing Letters is an international journal that promotes fast exchange of the current state-of-the art contributions among the artificial neural network community of researchers and users. The Journal publishes technical articles on various aspects of artificial neural networks and machine learning systems. Coverage includes novel architectures, supervised and unsupervised learning algorithms, deep nets, learning theory, network dynamics, self-organization, optimization, biological neural network modelling, and hybrid neural/fuzzy logic/genetic systems. The Journal publishes articles on methodological innovations for the applications of the afore mentioned systems in classification, pattern recognition, signal processing, image and video processing, robotics, control, autonomous vehicles, financial forecasting, big data analytics, and other multidisciplinary applications.
Keywords: Artificial intelligence; System theory; Computational intelligence; Artificial Intelligence; Complex Systems; Computational Intelligence